1998
DOI: 10.1016/s1074-7613(00)80650-0
|View full text |Cite
|
Sign up to set email alerts
|

Target Specificity of Immunoglobulin Class Switch Recombination Is Not Determined by Nucleotide Sequences of S Regions

Abstract: We describe a model system for class switch recombination (CSR) using CH12F3-2 cells transfected with a DNA construct containing two S sequences transcribed by different promoters and separated by a viral thymidine kinase (TK) gene. Recombination observed using this system shares key properties with physiological CSR: deletion of DNA between two S regions, requirement for cytokine stimulation, and nonhomologous and no consensus breakpoint sequences. Studies on transfectants with variants of this construct led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
49
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 51 publications
6
49
2
Order By: Relevance
“…Previously, we described an artificial CSR substrate in which each of two S regions was directed by a different constitutive promoter, and transcripts were spliced (22). This study demonstrated that the isotype specificity of CSR was not determined by the nucleotide sequences of S regions.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Previously, we described an artificial CSR substrate in which each of two S regions was directed by a different constitutive promoter, and transcripts were spliced (22). This study demonstrated that the isotype specificity of CSR was not determined by the nucleotide sequences of S regions.…”
mentioning
confidence: 82%
“…This plasmid was digested with restriction enzymes to generate a fragment containing the whole transcription unit as SR␣-TM-GFP. The BOS-EC-SS fragment and the SR␣-TM-GFP were connected on a plasmid with the neomycin-resistance gene cassette pSMC-11 (22), which is derived from pMC1neopolyA (Stratagene). The recombinants with the two transcription units in the opposite directions were designated as pSCR(0,0).…”
Section: Construction Of Inversion-type Class-switch Substrates Andmentioning
confidence: 99%
“…Genomic DNA was purified from the same source after separation of RNA from TRIzol lysate. cDNA was synthesized with Superscript II (GIBCO) by using 2 g of total RNA and 1 g of poly d(T) [12][13][14][15][16][17][18] (Amersham Pharmacia) in a 20-l reaction volume, one twentieth of which was used as a template for reverse transcription (RT)-PCR in a 25-l reaction volume. Amplification of AID transcripts was done by an initial denaturing step of 94°C for 5 min followed by 22 cycles of PCR (94°C for 20 s, 58°C for 30 s, 72°C for 1 min) by using recombinant Taq polymerase (Takara) with a 119-and 118-primer pair (11).…”
Section: Methodsmentioning
confidence: 99%
“…Isotype class switching in activated B cells illustrates this capability. The location of class switch recombination (CSR) is determined by lymphokine signals that control the transcription of "switch" regions where the necessary double-stranded breaks occur [190,191]. In other words, the immune system instructs the activated B cells which class of antibody to produce in response to a particular infection by targeting a specific DNA breakage-and-joining process.…”
Section: Targeting Of Nge and Mobile Elementsmentioning
confidence: 99%